Growth Performance of the Seedlings of Four Acacia Species Raised in Compost-Amended Sandy and Silty Soils - Daldoum , Daldoum M.A.; Ameri, Hakim A. (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of this study was to determine the effects of compost on growth of Acacia nilotica, A. seyal, A. senegal and A. tortilis seedlings. It was conducted in Khartoum University Farm, during December 1999- January 2002. Compost was prepared in a pit from forest litter and poultry manure. Four quantities of compost were added to a sandy soil and a silty soil (% volume): zero, 25%, 50% and 75%. The blends were packed in polythene bags prior to transplanting. The compost was slightly acidic, non-saline, and rich in nutrients and had high water holding capacity. The compost negatively affected acacia seed germination percentage by 1.5 to 5.3 folds compared to the mineral soils. Shoot height in the compost-sand mixes increased significantly as compared to the unamended sandy soil by 1.4 to 2 folds. Root length was generally lower in the compost treatments. Shoot and root biomass in the compost media was significantly higher than in the sandy soil and increased by 3 to 7 and 1.5 to 3.0 folds, respectively. In the silt-compost mixes, seedlings' shoot heights were significantly greater than in the unamended silty soil. Root lengths in the silt-compost mixes were not significantly different from those in the silty soil. Shoot and root biomass in the silt-compost mixes was not significantly different from that in the unamended silty soil. Compost effects on seedlings’ growth occurred in